Design of an Unmanned Surface Vehicle Based on Pixhawk Autopilot for Water Sampling - Masyhur, Abdullah Al; Setiawan, Muhammad Aldo; Achmad, Achmad; As’ad, Muhammad Ridwan (Journal of Advanced Technology and Multidiscipline, 2025)
Water is an important element in the life of living creatures, both for consumption and other purposes. Therefore clean water is crucial for human health and environmental protection. To determine the quality of water, whether it is safe for consumption or not, testing in a laboratory is required by testing the chemical elements and physical elements. This is because there are differences in determining whether water is suitable for use or not, the depth of the water also influences the differences in water quality, therefore we need the process of taking the water to be tested. Currently this process is carried out manually using manned vessels, this causes inefficiencies if carried out continuously. To overcome this problem, we need a tool that can collect water automatically. Unmanned Surface Vehicle (USV) is a vehicle that can walk on the surface of the water without passengers and can run manually using a Radio Control (RC) transmitter or automatically using the Pixhawk autopilot and Global Positioning System (GPS) as a localization system. This research aims to design an Unmanned Surface Vehicle (USV) that can take water samples automatically using the Pixhawk autopilot at a certain point and at a certain depth.